2006
DOI: 10.1177/0748233706070312
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of industrial solvents using human cell bioassays: assessment of short-term cytotoxicity and long-term genotoxicity potential

Abstract: There is an increasing demand for simple toxicological screening methods to assess the human health risk associated with exposure to environmental toxicants. Such screening tools should allow for risk evaluation in terms of both short-term/acute toxicity and longer-term genetic damage, which may lead to mutagenicity and carcinogenicity. We employed a battery of human cell bioassays using the human hepatoma cell-line, HepG2, to assess the cytotoxic and genotoxic potential of environmental pollutants. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To test our hypothesis, we have first assessed the potential effect of three camel urines, obtained from, lactating, pregnant and virgin camels, on the induction of Cyp1a1 by TCDD using EROD as a probe for Cyp1a1 activity in Hepa 1c1c7 cells (Hasspieler et al, 2006). Our results showed that all the three camel urines tested altered EROD activity to varying extents in a urine-dependent fashion.…”
Section: Discussionmentioning
confidence: 92%
“…To test our hypothesis, we have first assessed the potential effect of three camel urines, obtained from, lactating, pregnant and virgin camels, on the induction of Cyp1a1 by TCDD using EROD as a probe for Cyp1a1 activity in Hepa 1c1c7 cells (Hasspieler et al, 2006). Our results showed that all the three camel urines tested altered EROD activity to varying extents in a urine-dependent fashion.…”
Section: Discussionmentioning
confidence: 92%
“…Thus Cyp1a1 induction is considered a useful biomarker of exposure to carcinogenic substances [26]. Accordingly, we have first examined the potential effect of camel milk on the expression of Cyp1a1 gene after induction by TCDD using EROD as a probe for Cyp1a1 activity [27]. Our results showed that camel milk (fat-free) at all concentrations tested reduced Cyp1a1 EROD activity in a concentration-dependent manner (Figure 2).…”
Section: Discussionmentioning
confidence: 99%